A phase II study of cisplatin plus vinorelbine combined with atezolizumab as adjuvant therapy for completely resected non-small-cell lung cancer with EGFR mutation (West Japan Oncology Group 11719L/ADJUST study). (January 2021) - Shibaki, Ryota; Akamatsu, Hiroaki; Kato, Terufumi; Nishino, Kazumi; Okada, Morihito; Mitsudomi, Tetsuya; Wakuda, Kazushige; Yoshimura, Kenichi; Yamamoto, Nobuyuki; Nakagawa, Kazuhiko
Background: Epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitor (TKI) is a standard treatment in EGFR- mutated advanced non-small-cell lung cancer (NSCLC); however, previous data have suggested that EGFR-TKI has limited potential as adjuvant therapy. On the contrary, based on subset analysis with the immune checkpoint inhibitor (ICI) plus platinum-doublet chemotherapy in advanced NSCLC with EGFR mutation, we hypothesized that this combination was worth testing as adjuvant therapy in patients with EGFR- mutated NSCLC. Methods: Herein, we introduce our phase II study of cisplatin plus vinorelbine combined with atezolizumab as adjuvant therapy for completely resected NSCLC with EGFR mutation. Accrued patients will be pathological stage II–IIIA with completely resected NSCLC and whose tumors have EGFR mutation. Treatment comprises four cycles of cisplatin plus vinorelbine combined with atezolizumab followed by maintenance with atezolizumab. The primary endpoint is the disease-free survival (DFS) rate at 2 years. Secondary endpoints are DFS, overall survival, and safety. In total, 18 patients will be enrolled in this study. Discussion: Ongoing phase III trials of adjuvant ICI allow the inclusion of patients with EGFR mutation, but our current trial will provide the earliest clinical data on the efficacy of platinum-doublet chemotherapy with atezolizumab.